The Study of Relative Clauses in Azeri Turkish and Persian: A Typological Approach - Anita Bazian; Arsalan Golfam; Hayat Ameri (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
Typology which is one of the dynamic branches of linguistics tries to compare languages and attain generalizations. This approach aims at comparing languages’ structures and revealing systemic patterns of variations existing among them. Word order studies is one of the most important issues in language typology which includes some variations. The order of noun and relative clause is one of those which correlates with the main word order of languages. This study aims to look into relative clauses in Azerbaijani Turkish and compare them with that of Persian. For an efficient research, data has been collected from natural recurring sentences of spoken and written standard Turkish as well as a novel titled Shaman. Afterwards, the data has been judged by the speakers’ language instinct. Then every relative clause has been examined carefully. This article which is descriptive-analytic is done within the typological framework based on the work of Comrie (1989) to answer the questions of “what strategies have been conducted to construct relative clauses and where the relativizer can sit”. According to the findings of this research Turkish relative clauses benefit from gap strategy and this language lacks a relativizer like “ke” in Persian.IntroductionLanguage Typology, a dynamic branch of linguistics, seeks to achieve generalizations by comparing different languages. It aims to compare language structures and uncover systematic patterns of variation among them. One of the most significant areas of study in language typology is word order, which includes various types of variations. The order of the noun and relative clause is one such variation that correlates with the main word order in languages.     In an externally-headed relative clause, the head noun appears in the main clause. Consequently, the relative clause may contain a gap, a pronoun, or a full repetition of the head noun in relation to the reference noun. Externally-headed relative clauses can be either postnominal (as in Persian) or prenominal (as in Turkish). From a syntactic perspective, relative clauses differ significantly across languages, such as being finite or non-finite, which serves as a typological parameter.     This study aims to examine relative clauses in Azerbaijani Turkish and compare them with those in Persian. This descriptive-analytic project is conducted within a typological framework based on the work of Comrie (1989) to address the questions: “What strategies are used to construct relative clauses, and where can the relativizer be positioned?” in Azerbaijani Turkish.     Several studies have been conducted on relative clauses in Persian and Turkish. Aghaei (2006) and Taghvaeipoor (2014) argue that Persian externally-headed relative clauses, which feature an obligatory relativizer “ke,” are formed using gap or pronoun retention strategies. Kouhbanani et al. (2018) state that Persian includes both headed and headless relative clauses, while Khani and Mirdehghan (2019) consider Turkish to have prenominal relative clauses. In the Turkish relativization process, the verb changes into a participle.MethodologyThis research aims to describe relative clauses in Azerbaijani Turkish and compare them with those in Persian. The study is a descriptive-analytic project conducted within a typological framework based on Comrie’s (1989) approach. To ensure an effective analysis, data was collected from naturally occurring sentences in both spoken and written standard Turkish, as well as from a novel titled Shaman. The collected data was then verified through the linguistic intuition of native speakers. Each relative clause was carefully examined. Among 1,450 sentences from the novel Shaman, 100 relative clauses were identified and analyzed. The selection of relativizing affixes used for relativization was based on their practicality and frequency of use.ResultsThis research sought to answer two main questions: (1) What strategies are used to construct relative clauses? (2) Where can the relativizer be positioned in the relative clause?     The results show that Persian employs both gap and pronoun retention strategies in relativization, while Turkish uses only the gap strategy. In Persian relative clauses, “ke” serves as the relativizer; however, Turkish lacks a specific relativizer. Additional findings reveal that both Persian and Turkish are SOV (subject-object-verb) languages. However, Persian is a head-initial language, while Turkish is head-final. Persian relative clauses are postnominal and finite, whereas Turkish relative clauses are prenominal and non-finite.     Moreover, Turkish has borrowed significantly from the Persian language, leading to a substantial influence on Turkish. For example, Turkish has adopted the use of “ke” to form pronominal relative clauses, in addition to its prenominal relative clauses.